Aplikasi Sistem Presensi Karyawan Secara Online Pada PT Svarna Dipa Green Garden Jakarta Barat Berbasis Web dengan Metode Location Based Service menggunakan PHP - Sekali, Jessy Imel Natasa Karo; Faizah, NM; Koryanto, Lucky (Yayasan Kawanad, 2024)
The advancement of information technology has provided various facilities that positively impact organizational activities. Rapidly evolving information technology is expected to facilitate users in obtaining information. This information is used by companies as a basis for future planning and decision-making. PT Svarna Dipa Green Garden, a major company in Indonesia located in Cengkareng, West Jakarta, was established in 2018 and operates as an electronic distribution agent. Despite being a large company, the employee attendance system at PT Svarna Dipa Green Garden remains manual, using WhatsApp for communication between employees and supervisors. This manual system causes issues such as unstructured attendance data recording and difficulties in creating summary reports of attendance, leave, and overtime data. This study aims to develop a web-based employee attendance application with Location Based Service (LBS) using PHP framework Laravel and MySQL. The application will be tested using the black-box method to identify and evaluate errors. The implementation of this application aims to simplify attendance activities, leave applications, and data management, as well as facilitate report creation at PT Svarna Dipa Green Garden, West Jakarta.